Elucidation of the active conformation of the amino terminus of receptor-bound secretin using intramolecular disulfide bond constraints - Dong, Maoqing (2010)
Family B G protein-coupled receptors include several potentially important drug targets, yet our understanding of the molecular basis of ligand binding to and activation of these receptors is incomplete. While NMR and crystal structures exist for peptide ligand-associated amino-terminal domains of several family members, these only provide insights into the conformation of the carboxyl-terminal region of the peptides. The amino-terminal region of these peptides, critical for biological activity, is believed to interact with the helical bundle domain, and is, therefore, unconstrained in these structures. The aim of the current study was to provide insights into the conformation of the amino terminus of secretin as bound to its receptor. We prepared a series of conformationally-constrained secretin peptides containing intramolecular disulfide bonds that were predicted by molecular modeling to approximate the conformation of the analogous region of PACAP bound to its receptor that had been determined using transfer-NOE NMR techniques. Secretin peptides with pairs of cysteine residues in positions 2–7, 3–5, 3–6, 4–7, 7–9, and 4–10 were studied as linear and disulfide-bonded forms. The analogue with a disulfide bond connecting positions 7–9 had binding affinity and biological activity similar to natural secretin, supporting the relevance of this constraint to its active conformation. While this feature is shared between secretin and PACAP, absence of activity in other constrained peptides in this series also suggest that there are differences between these receptor-bound conformations. It will be critical to extend similar studies to other family members to learn what structural elements might be most conserved in this family.